Da concepção de um polo cloroquímico ao desenvolvimento da cadeia produtiva da química e do plástico de Alagoas - Diodato, Railson Vieira (2017)
The petrochemical industry is considered an industrial sector that has great influence in the development and relationships with other economic sectors. The Alagoas Chlorochemical Pole (PCA) has the presence of the sixth largest petrochemical company in the world, Braskem, which operates the largest chlorine soda processing plant and the largest PVC producer in Latin America, making it possible for the state of Alagoas to strengthen Its Chemical and Plastic Production Chain (CPQP). Through historical periodizations, this research deals with the formation of the Chlorochemical Pole of Alagoas (PCA) and the current Chemical and Plastic Production Chain (CPQP) of the state. The implementation of the chemical industry center in Alagoas and the role of the agents involved in this implementation were analyzed, as well as the data on the Chemical and Plastic Production Chain of Alagoas. With the objective of establishing a profile of the CPQP of Alagoas, the size of the companies was measured, the region of origin of the raw material and the destination of production, as well as the distribution of the number of employees by economic activity and by metropolitan regions Of Maceio and Agreste. The development of the research was based on the perspective of critical geography, using for the theoretical foundation: Santos (1982), Perroux (1967) and Cholley (1964). The categories of analysis used in this research were as follows: Socio-spatial Formation, Santos (1982); Geological Combinations, by Cholley (1964); And Growth Poles Theory, by François Perroux (1967). The study discusses the socio-spatial, the geographical combinations that led to the formation of an immense deposit of the ore salgema in the state, the influence of the National Development Plans for the formation of the PCA and analyzes the current CPQP of Alagoas.